Strategic Values in Madrasa Development in Kudus: Management Study of Islamic Education Perspective in Nusantara - Kisbiyanto, K; Setyoningsih, S (LPPM IAIN Kudus, 2018)
This study aims to explain the basic values of madrasa management in Kudus, the values of developing madrasa in Kudus, and the excellent values of madrasa in Kudus. This research is a field study that uses a qualitative approach. Data collection uses interview, observation, and document study methods. Data analysis used the Spradley model, namely domain, taxonomic, compound, and cultural themes analysis. The result of this study explains that the strategic values in the madrasa lie in the basic values of the madrasa i.e. an educational institution whose main mission is to teach the islamic sciences. The next strategic values are the values of development which focus on a better quality learning model, namely curriculum, learning and output. Furthermore, the excellent values of the madrasa are focused on three values, namely the values of excellence in tafaqquh fiddin or mastery in the knowledge of Islam, the values of excellence in memorizing the Qur'an, and the values of excellence in the field of research. It is recommended that the madrasah aliyah in Kudus also develop other strategic values to become excellent, such as international schools or ICT based schools.